Enhanced molecular visualization of root colonization and growth promotion by Bacillus subtilis EA-CB0575 in different growth systems (2018)
Bacillus subtilis EA-CB0575 is a plant growth-promoting bacterium (PGPB) associated with banana and tomato crops. Root colonization is an important trait for PGPB microorganisms and potentiates the bacterial effect related to the mechanisms of plant growth promotion. Therefore, detection of bacterial colonization of roots in different culture systems is important in the study of plant–microorganism interactions. In this study, fluorescent in situ hybridization (FISH) and catalyzed reporter deposition–FISH (CARD–FISH) were evaluated to determine the colonization ability of B. subtilis EA-CB0575 on banana and tomato roots planted on solid and liquid Murashige and Skoog medium (MS(S) and MS(L), respectively) and in soil for tomato plants. Results showed B. subtilis colonization 0–30 days post inoculation for banana and tomato plants in different culture systems with differential distribution of bacterial cells along tomato and banana roots. FISH and CARD–FISH methodologies were both successful in detecting B. subtilis colonies, but CARD–FISH proved to be superior due to its enhanced fluorescence signal. The presence of bacteria correlated with the promotion of plant growth in both plant species, providing clues to relate rhizospheric colonization with improvement in plant growth. FISH and CARD–FISH analysis results suggested the presence of native microbiota on the roots of in vitro banana plants, but not on those of tomato plants. © 2018 Elsevier GmbH